2012
DOI: 10.1093/fampra/cmr127
|View full text |Cite
|
Sign up to set email alerts
|

German GPs' willingness to expand roles of physician assistants: a regional survey of perceptions and informal practices influencing uptake of health reforms in primary health care

Abstract: The increasing proportion of women in family medicine might favor task shifting in General Practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 28 publications
2
31
0
12
Order By: Relevance
“…Our response rate is comparable or better to other studies conducted in Germany or the Netherlands [12,31]. Compared to the GP population of a rural area of Germany, the Berlin source population has a similar age distribution and fairly similar distribution of individual and group practices [42,43]. Similarly, a study that investigated GPs’ willingness to delegate primary prevention tasks to physician assistants found that GPs consider lifestyle counseling as part of their task.…”
Section: Discussionsupporting
confidence: 75%
“…Our response rate is comparable or better to other studies conducted in Germany or the Netherlands [12,31]. Compared to the GP population of a rural area of Germany, the Berlin source population has a similar age distribution and fairly similar distribution of individual and group practices [42,43]. Similarly, a study that investigated GPs’ willingness to delegate primary prevention tasks to physician assistants found that GPs consider lifestyle counseling as part of their task.…”
Section: Discussionsupporting
confidence: 75%
“…12 The issue of task shifting from GP to practice assistant or advanced nurse practitioner is the subject of current debate in many countries. [13][14][15] Our analysis of the monthly prevalence in relation to the setting in which care was provided showed the high number of people who had received medical care at home: in the previous month, more than 14% of the population had received a home visit from a doctor. This is not a new observation, as several studies have already highlighted this characteristic of the Belgian health care system: each Belgian person on average receives 1.6 home visits per year, the majority of which are conducted by GPs, compared to 2.7 consultations in the doctor's office and 2.1 consultations in a specialist clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study of Dini et al showed that 48% of general practitioners in Germany inclined to delegate home visit tasks to their practice assistants. The main disadvantage here was the related costs for training of the practice assistants, while the ability to save time was named as the main advantage [23]. To realise task substitution in Germany there are for example the so called ‘AGnES-model projects’ in different federal states, which transfer medical duties and house visits to qualified practice assistants.…”
Section: Discussionmentioning
confidence: 99%